Between the purposefulness of the Shari‘ah and normativity - El-Mesawi, Mohamed El-Tahir (2010)
The present study is an attempt at reconstructing the views of Abu Ishaq al-Shatibi and Ibn Khaldun into one coherent theoretical framework for the understanding of human socio-historical existence. Being contemporaries who lived in the eighth/fourteenth cen-tury under almost similar socio-political and cultural conditions that prevailed in North Africa and Andalus, both scholars embarked on an ambitious project of radical reform. A jurist by training and profession who was dissatisfied with the legal hermeneutic methodology of Muslim jurists, al-Shatibi was concerned about developing a holistic approach to the study and interpretation of Islam’s textual sources (the Qur’an and the Prophet’s Sunnah) with a view to discovering the fundamental values and universal principles underlying the Shari‘ah ethico-legal system governing human socio-historical existence as a multifaceted and dynamic reality. His effort culminated in his widely acclaimed theory of the Shari‘ah objectives (maqasid al-Shari‘ah) that consisted in developing a new and comprehensive legal hermeneutics whereby Islamic spiritual, moral and legal teachings are seen to revolve around realizing and promoting five necessary universal objectives. .....